The impact of socioeconomic status on the burden of foodborne illnesses: a scoping review in the Middle East and North African region - Al Khatib, Alissar; Kabir, Russell (Frontiers in Microbiology, 2025)
BackgroundFoodborne diseases remain a significant global health concern. Conversely, socioeconomic status represents a crucial predictor of diseases with increased morbidity and mortality rates. This scoping review (ScR) aims to provide an understanding of the impact of socioeconomic status on the occurrence of foodborne illnesses in the Middle East and North Africa (MENA) region.MethodologyThree databases (Medline [PubMed], Web of Science, and Embase) were searched on 24 August 2024, for articles published in English. The population, concept, and context (PCC) framework was adopted in this review.ResultsA total of 1,667 records were identified. After removing 530 duplicates, 1,137 records were screened for inclusion. Twelve studies were eligible after excluding records with reasons. Of the 12 studies, 11 were cross-sectional studies and 1 was a case–control in design. The studies were conducted in countries of the MENA region, including Saudi Arabia, Qatar, the United Arab Emirates, Palestine, Lebanon, Egypt, and Iran. Low income was generally associated with higher rates of parasitic infections among populations in Egypt, Palestine, Lebanon, and one study in Iran. The relationship between the level of education and infection rates was divergent. In some studies, individuals with lower education levels have shown higher infection rates, as seen in Egypt, Iran, and Qatar; however, other studies found no significant association. Occupation appeared to be less consistently related to infection rates. Food handlers had the highest rates of infection in the UAE, while studies from other regions did not find significant associations. Giardia lamblia (33%) and Blastocystis hominis (26%) were found to be the predominant intestinal parasites in the included studies.ConclusionThis scoping review emphasizes discrepancies between studies on the impact of socioeconomic status affects the rate of intestinal infection. Thus, future research should provide clear definitions and indicators of socioeconomic metrics and address the occurrence of foodborne illnesses in terms of cultural factors, healthcare inequality, and food insecurity.